2010
DOI: 10.1001/archinternmed.2010.153
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of a Score to Assess Risk of Adverse Drug Reactions Among In-Hospital Patients 65 Years or Older

Abstract: This study proposes a practical and simple method of identifying patients who are at an increased risk of an ADR. This approach may be useful in clinical practice as a tool to identify patients at risk and in research to target a population that can benefit from interventions aimed to reduce drug-related illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
354
5
17

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 272 publications
(402 citation statements)
references
References 38 publications
26
354
5
17
Order By: Relevance
“…Indeed, the chance of an adverse drug event during the hospitalization of an older adult taking 8 or more medications is greater than 85%. 27 Medications can be safely stopped in older adults, with improved functional outcomes in the outpatient setting. 28 Reduction in polypharmacy should target three classes of medications: anticholinergics, proton pump inhibitors (PPIs), and benzodiazepine and nonbenzodiazepine hypnotics.…”
Section: Preventing Adverse Drug Events By Minimizing Polypharmacymentioning
confidence: 99%
“…Indeed, the chance of an adverse drug event during the hospitalization of an older adult taking 8 or more medications is greater than 85%. 27 Medications can be safely stopped in older adults, with improved functional outcomes in the outpatient setting. 28 Reduction in polypharmacy should target three classes of medications: anticholinergics, proton pump inhibitors (PPIs), and benzodiazepine and nonbenzodiazepine hypnotics.…”
Section: Preventing Adverse Drug Events By Minimizing Polypharmacymentioning
confidence: 99%
“…It has been reported that the risk factors for adverse drug reactions (ADRs) are the presence of heart failure, liver disease, the number of medications, previous ADR, renal failure, and ≥4 comorbid conditions . 21 Almost all the patients who admit to acute hospital have those problems; thus, we have to think more about ADRs.…”
Section: Discussionmentioning
confidence: 99%
“…Two approaches have been recently reported in the literature which identify older patients at high risk for developing ADRs, both of which are simple and efficient: the GerontoNet ADR risk score [24] and the Brighton Adverse Drug Reactions Risk (BADRI) Model [25].…”
Section: Identification Of Older Patients At Risk For Developing Advementioning
confidence: 99%